Biochemical components and dry matter of lemon and mandarin hybrids under salt stress - Francisco V. da S. Sá; Marcos E. B. Brito; Lizaiane C. de Figueiredo; Alberto S. de Melo; Luderlândio de A. Silva; Rômulo C. L. Moreira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective was to study the biochemical changes and dry matter content in lemon and mandarin hybrids under salt stress during rootstock formation. For this, a study was conducted in randomized complete block, using a 2 x 5 factorial scheme, with two salinity levels (0.3 and 4.0 dS m-1) applied in five citrus rootstock genotypes (1. TSKC x CTARG - 019; 2. LRF; 3. TSKC x (LCR x TR) - 040; 4. LCRSTC and 5. LVK), with three replicates and four plants per plot. At 90 days after sowing, saline treatments started to be applied and continued until 120 days after sowing, the moment in which the plants were collected for evaluation of biochemical characteristics and phytomass accumulation. The increase in water salinity negatively affected the biochemical components and dry matter accumulation of citrus genotypes. The genotypes TSKC x (LCR x TR) - 040, LCRSTC and LVK were the least affected by salt stress, standing out as the materials most tolerant to salinity.